1993
DOI: 10.1111/j.1439-0434.1993.tb01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Development of Grey Mould (Botrytis cinerea) in Bean and Tomato Plants by Calcium Nutrition

Abstract: Fertilization of bean plants grown in perlite with 1 and 3 mM CaCl2 or Ca(NO3)2 reduced severity of grey mould as compared with control plants or plants fertilized with 5 mM of the compounds. Fertilization with Ca(NO3)2 reduced severity leaf grey mould and fruit ghost spots of tomato plants grown in perlite by 70 and 45%, respectively. The rate of decrease varied with the position of the fruits on the plants. Leaves from plants treated with calcium or otherwise [KNO3, (NH4)2SO4] produced less ethylene than lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Calcium ions in the form of sulphate (CaSO 4 ), chloride (CaCl 2 ) or nitrate (CaNO 3 ) were reported to suppress B. cinerea pre‐ and postharvest in numerous crops (Volpin & Elad, 1991; Conway et al ., 1993; Elad & Volpin, 1993; Starkey & Pedersen, 1997; Baas et al ., 2000; Bar‐Tal et al ., 2001; Capdeville et al ., 2003). The Ca content of plant tissues may affect host susceptibility in two ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium ions in the form of sulphate (CaSO 4 ), chloride (CaCl 2 ) or nitrate (CaNO 3 ) were reported to suppress B. cinerea pre‐ and postharvest in numerous crops (Volpin & Elad, 1991; Conway et al ., 1993; Elad & Volpin, 1993; Starkey & Pedersen, 1997; Baas et al ., 2000; Bar‐Tal et al ., 2001; Capdeville et al ., 2003). The Ca content of plant tissues may affect host susceptibility in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, variable effects may be observed at different stages of the pathogen's life cycle. With respect to grey mould, high nitrogen rates were reported to increase, decrease, or not change the susceptibility of various host plants to B. cinerea (Hobbs & Waters, 1964; Verhoeff, 1968; Hoffland et al ., 1999; Dik & Wubben, 2004), while high calcium rates are generally associated with reduced susceptibility to B. cinerea (Volpin & Elad, 1991; Elad & Volpin, 1993; Starkey & Pedersen, 1997; Baas et al ., 2000; Bar‐Tal et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study showed that treatments that increased Ca concentration in the plant reduced the susceptibility of the flower to a sprayed conidial suspension, which exposed the flowers to extreme attack by the disease. Although the correlation of petal Ca concentration with the susceptibility to B. cinerea was not very high, there is enough evidence in the literature that Ca is involved in the resistance mechanism of the plant to infection by this disease [10,12,29] as well as in the post-harvest flower longevity and bud opening [23] and senescence process [28]. Other environmental factors like radiation, humidity and temperature [21,30] and internal factors like ethylene [8,10,29] are also involved in the susceptibility to B. cinerea.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium nutrition of plants has reduced grey mould incidence on several crops [12,13,33] including cut rose [29] and potted rose [27]. The ability of B. cinerea to produce polygalacturonase and to thrive on Na-pectate as a sole carbon source is reduced if CaCl 2 is added to liquid cultures [29].…”
Section: Introductionmentioning
confidence: 99%
“…Commercially blended fertilizers that contain high concentrations of NH 4 + are lower in Ca (Nelson, 1996). High levels of Ca and K have significant influence on disease resistance (Elad and Volpin, 1993;Marshner, 1995;Mengel and Kirby, 2001). Calcium has a major physiological role in forming the cell membrane and cell wall, which protects against pathogens (Elad, 1988;Elad and Evensen, 1995;Volpin and Elad, 1991).…”
mentioning
confidence: 99%